An EEG–MEG Dissociation between Online Syntactic Comprehension and Post Hoc Reanalysis - Meltzer, Jed A.; Braun, Allen R. (Frontiers in Human Neuroscience, 2011)
Successful comprehension of syntactically complex sentences depends on online language comprehension mechanisms as well as reanalysis in working memory. To differentiate the neural substrates of these processes, we recorded EEG and MEG during sentence picture matching in healthy subjects, assessing the effects of two difficulty factors: syntactic complexity (object-embedded vs. subject-embedded relative clauses) and semantic reversibility on neuronal oscillations during sentence presentation, and during a subsequent memory delay prior to picture onset. Synthetic Aperture Magnetometry analysis of MEG showed that semantic reversibility induced left lateralized perisylvian power decreases in a broad frequency range, approximately 8-30 Hz. This effect followed the relative clause presentation and persisted throughout the remainder of the sentence and the subsequent memory delay period, shifting to a more frontal distribution during the delay. In contrast, syntactic complexity induced enhanced power decreases only during the delay period, in bilateral frontal and anterior temporal regions. These results indicate that detailed syntactic parsing of auditory language input may be augmented in the absence of alternative cues for thematic role assignment, as reflected by selective perisylvian engagement for reversible sentences, compared with irreversible sentences in which world knowledge constrains possible thematic roles. Furthermore, comprehension of complex syntax appears to depend on posthoc reanalysis in working memory implemented by frontal regions in both hemispheres.